Enhancing Technological Literacy of Students and Teachers through Robotics and Introduction to Artificial Intelligence - Riska Ekawita; Iwan Setiawan; Ashar Muda Lubis; Yazid Ismi Intara; Irkhos Irkhos; Siti Hairunnisa Norfahmi (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2026)
Background: Robotics technology has evolved from merely representing technological progress to becoming an essential component of modern learning, supporting students’ creativity and logical reasoning. However, SMAN 8 Seluma faces limitations in its facilities and infrastructure, which prevent the integration of robotics and artificial intelligence (AI) into the learning environment. Purpose of the Study: To overcome this issue, a community service program was conducted to provide robotics training and AI introduction to 25 students and 3 teachers. Methods: The methods employed included the introduction of robot components, robot assembly practice, sensor development, and AI fundamentals. Results: From the activities, the participant groups successfully assembled a fully functional robot. The questionnaire results indicated a clear increase in students’ knowledge before and after the program. The pre-test results showed that 10% of participants were not familiar with robotics. Following the training sessions, this proportion improved to 100%, indicating that all participants had acquired an understanding of robotics. A similar pattern was observed for artificial intelligence (AI), where 30% of participants were initially unfamiliar with the technology; however, after the program, 100% of participants demonstrated an understanding of AI concepts)